Community pharmacists’ perspectives on cardiovascular disease pharmaceutical care in the United Arab Emirates: a questionnaire survey-based analysis - Jairoun, Ammar Abdulrahman; Al-Himyari, Sabaa Saleh; Shahwan, Moyad; Al Ani, Mina; Habeb, Mustafa; Jairoun, Maimona; Zyoud, Sa’ed H.; Alkhanani, Mustfa Faisal; Alhasani, Reem Hasaballah; Hakami, Alqassem Y.; Ainousah, Bayan A.; Alshehri, Fahad S.; et al. (Frontiers in Pharmacology, 2023)
Background: Community pharmacists play an intermediary role between prescribing physicians and patients in the United Arab Emirates (UAE) and thus are responsible for ensuring that patients receive optimal cardiovascular disease (CVD) pharmaceutical care.Methods: we used a cross-sectional design to assess the perceptions and practices of community pharmacists concerning pharmaceutical care for patients with CVD. A trained researcher visited randomly selected community pharmacies and used a structured questionnaire to conduct in-person interviews with pharmacists. The questionnaire collected demographic data and information on perceptions and practices regarding CVD pharmaceutical care. Results: Five hundred and fifty-one participants were recruited. The average participant age (mean ± SD) was 35 ±2.7 years. The average perception score regarding CVD prevention and management was 75.6% (95% confidence interval [CI] 77.1-74.2%), and the average practice score for CVD prevention and management was 87.1% (95% CI 76.5-79.6%). Bivariate analysis revealed that gender (P=0.001), education level (P<0.001), pharmacy position (P=0.004), work experience (P<0.001), number of patients served per day (P<0.001) and being trained on CVD prevention and management (P<0.001) were significantly associated with perceptions about the prevention and management of CVD. Better practice scores were seen among older participants (OR 1.01; 95% CI 1-1.019), postgraduates (OR 1.77; 95% CI 1.66-1.89), workers at chain pharmacies (OR 1.24; 95% CI 1.11-1.39), pharmacists in charge (OR 1.22; 95% CI 1.01-1.47), pharmacists with > 10 years of experience (OR 11.3;, pharmacists with 6-10 years of experience (OR 4.42; 95% CI 3.90-5) and pharmacists trained on CVD prevention and management (OR 1.29; 95% CI 1.15-1.46). Conclusion: Pharmacy practitioners working in community pharmacies in the UAE actively engage in delivering pharmaceutical care to patients, playing a role in CVD management and prevention. However, they showed low levels of involvement in other healthcare services, specifically in screening and measuring patients' weight, glucose levels, and blood pressure, monitoring treatment responses, maintaining medical records, and reviewing medication refill histories. Activities such as educating patients, providing medication counseling, offering support for treatment adherence, and fostering collaborative relationships with other healthcare providers should be encouraged among UAE community pharmacists to ensure the provision of high-quality patient care.